Prostate cancer health disparities: An immuno-biological perspective. (1st February 2018) - Kumar, Sanjay; Singh, Rajesh; Malik, Shalie; Manne, Upender; Mishra, Manoj
Abstract: Prostate cancer (PCa) is the most commonly diagnosed malignancy in males, and, in the United States, is the second leading cause of cancer-related death for men older than 40 years. There is a higher incidence of PCa for African Americans (AAs) than for European-Americans (EAs). Investigations related to the incidence of PCa-related health disparities for AAs suggest that there are differences in the genetic makeup of these populations. Other differences are environmentally induced (e.g., diet and lifestyle), and the exposures are different. Men who immigrate from Eastern to Western countries have a higher risk of PCa than men in their native countries. However, the number of immigrants developing PCa is still lower than that of men in Western countries, suggesting that genetic factors are involved in the development of PCa. Altered genetic polymorphisms are associated with PCa progression. Androgens and the androgen receptor (AR) are involved in the development and progression of PCa. For populations with diverse racial/ethnic backgrounds, differences in lifestyle, diet, and biology, including genetic mutations/polymorphisms and levels of androgens and AR, are risk factors for PCa. Here, we provide an immuno-biological perspective on PCa in relation to racial/ethnic disparities and identify factors associated with the disproportionate incidence of PCa and its clinical outcomes. Highlights: PCa racial disparities in various populations are reviewed. Genetic/epigenetic and tumor biology factors involved in PCa racial disparities are summarized. Role of altered signaling, cytokines, and drug resistance mechanism are discussed. Role of tumor antigens as an alternative option for PCa therapy are elaborated. Role of various immune cells in the regulation of PCa health disparities has been discussed. Advance immunotherapies to improve PCa health disparities among AAs and EAs are discussed.